Mejía- Arauz, R., Rogoff, B., Dayton, A. & Henne-Ochoa, R. Collaboration or Negotiation: Two Ways of Interacting Suggest How Shared Thinking Develops, Current Opinion in Psychology, 2018, 23,117-123 - Aceiro, María Agustina (2018)
Fil: Aceiro, María Agustina. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina